Mosaicism: Reason for Normal Phenotypes in Carriers of Small Supernumerary Marker Chromosomes With Known Adverse Outcome. A Systematic Review - Liehr, Thomas; Al-Rikabi, Ahmed (Frontiers in Genetics, 2019)
Small supernumerary marker chromosomes (sSMCs) are present in ~3.3 million of presently living human beings. The majority of these sSMC carriers (i.e. ~2.1 million) will never know about their condition, as they are perfectly healthy and just may learn by chance about it, e.g. if chromosomal analysis is done for some reason during their life time. The remainder ~1.2 million of sSMC carriers are clinically affected either due to adverse effects of gained genetic material being present on the sSMC and/or by uniparental disomy of the sSMC’s sister chromosomes. Influence of mosaicism being present in 50% of sSMC carriers is controversy discussed in the literature. Even though genotype-phenotype correlation for sSMCs progressed during last years, still there are only 8 sSMC-associated syndromes characterized yet, which may go together with mosaicism. Here we summarize presently available data for carriers of sSMCs normally leading to these well-defined syndromes, however, showing (almost) no clinical signs. This can be observed in ~1 to 30% of the corresponding sSMC-carriers, thus, a high impact for counselling in corresponding prenatal de novo cases is not to be neglected.